Green's function and finite element formulations for the dynamics of pipeline conveying fluid - Soon, F.K. (Taylor and Francis Ltd., 2021)
Pipeline damage due to internal flow induced vibration is known to pose challenging problems in oil and gas industry. To reduce these problems, it is necessary to understand the vibration characteristics of the pipeline conveying fluid. The Winkler foundation is reported to have a stabilising effect to the pipeline structure in the literature. Therefore, in this study, dynamic analysis of pipeline conveying fluid mounted on the Winkler foundation is performed to obtain the force response of the pipeline. The partial differential equation of the pipeline conveying fluid subjected to several boundary conditions is solved numerically and analytically by using the finite element and Green's function method. The results of both methods are compared and validated against other numerical schemes and existing reported analytical data. The results indicate that Green's function is more accurate than finite element method in determining the forced response of the pipeline at a higher fluid velocity for simply supported and fixed supported pipeline. The findings in the present study provide the physical insight of the Coriolis force and Winkler foundation stiffness effect to the pipeline conveying fluid. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.